To rewrite the equation \( 5q^2 - 3q = 4q^2 - 5q + 15 \) in standard form, we need to move all terms to one side of the equation.
-
Start with the given equation:
\[ 5q^2 - 3q = 4q^2 - 5q + 15 \] -
Subtract \( 4q^2 \), add \( 5q \), and subtract \( 15 \) from both sides:
\[ 5q^2 - 4q^2 - 3q + 5q - 15 = 0 \] -
Combine like terms:
\[ (5q^2 - 4q^2) + (-3q + 5q) - 15 = 0 \] \[ q^2 + 2q - 15 = 0 \]
So, the equation in standard form is:
\[
q^2 + 2q - 15 = 0
\]
Now, let's solve the equation using factorization or the quadratic formula.
Factorization
-
Find factors of -15 that add up to 2:
The factors of -15 that work are 5 and -3. -
Rewrite the quadratic:
\[ (q + 5)(q - 3) = 0 \] -
Set each factor to zero:
\[ q + 5 = 0 \quad \Rightarrow \quad q = -5
\]
\[ q - 3 = 0 \quad \Rightarrow \quad q = 3 \]
Solutions
The solutions to the equation \( q^2 + 2q - 15 = 0 \) are:
\[
q = -5 \quad \text{and} \quad q = 3
\]
Thus, you have completed both parts: the equation in standard form is \( q^2 + 2q - 15 = 0 \) and the solutions are \( q = -5 \) and \( q = 3 \).